DISTRIBUSI MATERI GELAP GALAKSI PIRINGAN KERDIL DARI KURVA ROTASI UNIVERSAL - Ariana Sarashanti, Mifthanzi
Dwarf disc galaxy is a late-type spiral galaxy that only consists of a disc as the luminous component. Various studies show that dwarf disc galaxy is dom- inated by dark matter. Hence, this type of galaxies is suitable as an object for studies of dark matter distribution. The idea of a universal rotation curve (PSS, 1996) allows the study of the distribution of dark matter in dwarf disk galaxies based on luminosity and optical velocity groups without the need to decompose it individually. In this work, I synthesized universal rotation curves from several dwarf disc galaxies with a fainter range of absolute mag- nitude than PSS (1996) and more number of galaxies than Karukes & Salucci (2017). Data in this work was taken from SPARC and divided into three veloc- ity groups (Vopt 60 km/s, 60 km/s < Vopt < 80 km/s, 80 km/s < Vopt < 100 km/s) after being selected based on several criteria. Universal rotation curve of each velocity group was then decomposed to get its dark matter distribu- tion by employing metropolis-hastings Markov Chain Monte Carlo (MCMC) simulations using three halo models (isothermal non-singular, Burkert, dan NFW). The simulation results show that the universal rotation curve best t with the Burkert prole. Therefore, it can be concluded that dwarf disc galax- ies have a dark matter core at the center within the core radius the density of dark matter is constant, not cuspy as is expected in the case of NFW prole.